Self-Enforcing Power Sharing in Weak States. (28th March 2018) - Roessler, Philip; Ohls, David
Abstract: Power sharing, in which elites from rival societal groups agree to share control of the central government, is a key source of domestic peace, enabling states to escape devastating cycles of exclusion and civil war. Yet the conditions giving rise to inclusive governance are not well understood. In contrast to existing scholarship that emphasizes the importance of external third-party mediation or strong formal institutions, we point to the structural roots of power sharing in which political inclusion stems from the distribution of societal power and the balance of threat capabilities it produces. Only when both the ruling group and a given rival group possess strong mobilizational capabilities, such that each could credibly threaten to recapture state power if excluded from the central government, does self-enforcing power sharing emerge. A strong rival induces the ruler to commit to power sharing and to reluctantly accept coup risk over civil war risk. The ruling group's own threat capabilities, in turn, constrain rivals from trying to convert their share of power into absolute power. Supported by extensive quantitative and qualitative evidence with particular reference to weak states in sub-Saharan Africa, we shed light on the conditions under which the distribution of violence within a state underwrites a peaceful and productive equilibrium. In doing so, we rethink how scholars approach the study of civil war. Rather than conceiving of it in terms of effective resistance, we model civil war as a contest for state power shaped by groups' capabilities to project force in the capital.